Shock-induced turbulent mixing at high density ratios. - Probyn, Michael (Cranfield University, 2015)
Restricted under Crown Copyright. Only available to MOD students/employees with MOD ID (alternatively written permission from Supervisor or MOD). Contact library@cranfield.ac.uk to request access.